The letters of Claudius Terentianus and the new testament: insights and observations on epistolary themes - Head, PM (Tyndale House, 2014)
Eleven papyrus letters from the early second century (P. Mich. 467- 480 & inv. 5395) are studied in relation to parallel interests expressed within NT letters, on the topics of physical layout and formatting, discussions of health, the desire for news and the role of greetings, the role of the letter carrier and the use of letters of recommendation.